Financial Innovation and Risk, the Role of Information - Piazza, Roberto (IMF Working Papers; Working Paper ;, 2010)
Financial innovation has increased diversification opportunities and lowered investment costs, but has not reduced the relative cost of active (informed) investment strategies relative to passive (less informed) strategies. What are the consequences? I study an economy with linear production technologies, some more risky than others. Investors can use low quality public information or collect high quality, but costly, private information. Information helps avoiding excessively risky investments. Financial innovation lowers the incentives for private information collection and deteriorates public information: the economy invests more often in excessively risky technologies. This changes the business cycle properties and can reduce welfare by increasing the likelihood of "liquidation crises".